Agile and Resilient Civil Construction Project Scheduling - Abshari, Samira (International journal of industrial engineering and operational research, 2021)
The dynamic nature of civil construction projects demands adaptive scheduling techniques that can accommodate changing conditions, uncertainties, and stakeholder needs. Agile and resilient project scheduling methodologies have emerged as critical approaches for ensuring project success in the face of these challenges. This paper explores the principles, methodologies, and benefits of integrating agile and resilient practices in civil construction scheduling. A comprehensive review of existing literature, combined with case studies and numerical analyses, illustrates how these approaches enhance flexibility, reduce risks, and improve project outcomes. The findings highlight the importance of iterative planning, stakeholder collaboration, and contingency strategies in achieving robust scheduling frameworks. Practical recommendations are provided to guide construction managers in adopting these methodologies effectively.